Radiographic Study of Hip-Spine Alignment and Movement in Normal Volunteers - Goshi, Kohei; Ogawa, Hikaru; Sasaki, Kunio; Arimizu, Jun (Orthopedics & Traumatology, 2001)
Sagittal lumbopelvic alignment and compensations are important factors for consideration in degenerative lumbar diseases. Further understanding is needed on the functional relations between parameters of the pelvic and lumbar spine system. The objective of this study was to report hip-spine alignment and movement in normal subjects. We used lateral roentogenograms of the lumbar spine and pelvis, taking in standing, forward, and backward positions. Fifty normal volunteers without LBP were studied. The mean age was 35 years (SD, 7.6). Radiographic measurements were done using Jackson s method. The mean lordosis (LO) was 47 (SD, 8.9), mean sacral inclination (SI) was 34 (SD, 7.0), and mean pelvic angle (PA) was 15 (SD, 6.0) The mean range of motion of LO was 52, SI was 12, and PA was 12. There existed correlations (p<0.05) between LO and SI, and PA and SI, but not between LO and PA on range of motion.